2016
DOI: 10.1680/stbu.14.00127
|View full text |Cite
|
Sign up to set email alerts
|

Shear failure mechanism of composite concrete T-shaped beams

Abstract: The paper presents results of a study on T-shaped composite concrete beams with a variously located interface. Damage to tested beams was caused by shear. The crack patterns and the value of the force causing interface cracking were analysed. Conclusions concerning the failure mechanism were formulated. Moreover, the influence of the interface location and of the difference between the moduli of elasticity of joint materials on stress in the interface was also analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
4
15
0
Order By: Relevance
“…It has been widely demonstrated that it can significantly influence on the microcracking level and surface roughness, substrate saturation level and as a consequence it may affect the bond strength between repair material and concrete substrate [3,[13][14][15][16][17][18]. The effect of surface quality on impact-echo signal was investigated for two groups of concrete substrates ( Table 1).…”
Section: Concrete Substrate Quality and Bond Strength Of Tested Repaimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely demonstrated that it can significantly influence on the microcracking level and surface roughness, substrate saturation level and as a consequence it may affect the bond strength between repair material and concrete substrate [3,[13][14][15][16][17][18]. The effect of surface quality on impact-echo signal was investigated for two groups of concrete substrates ( Table 1).…”
Section: Concrete Substrate Quality and Bond Strength Of Tested Repaimentioning
confidence: 99%
“…Its quality is affecting the adhesion and as a consequence reliability and durability of repair [1][2][3]. Adhesion is understood as a process through which two bodies are brought together and attachedbonded -to each other: it has therefore two different aspects, according to whether interest is mainly either in the conditions and the kinetics of contact or in the separation process [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the last paper of this issue, Halicka and Jabłonski (2016) present an experimental investigation of T-shaped composite concrete beams. The investigation aims to study the influence of interface location on the behaviour of beams tested; the interface is located between the flange and the web, at the midheight and at a distance of one-quarter of the height from the bottom edge.…”
Section: Structures and Buildingsmentioning
confidence: 99%
“…The tests of composite beams [ 27 , 28 , 29 ] clearly show that apart from the adhesion conditions in the joint surface and the intensity of transverse reinforcement, the location of the contact at the cross-section height and the relationship between the stiffness of the base element (substrate) and the concrete overlay are important. Depending on the relation between the forces at cracking of the interface and at the shear crack formation, the failure may be initiated by cracking of the interface or proceed in the same way as in monolithic elements.…”
Section: Introductionmentioning
confidence: 99%